2011
DOI: 10.1177/1538192710397732
|View full text |Cite
|
Sign up to set email alerts
|

Filial Responsibility Expectations Among Mexican American Undergraduates: Gender and Biculturalism

Abstract: How Mexican American college students perceive responsibility for parental care is important as Mexican American elders’ numbers increase. The authors applied mixed methods to investigate the impact of gender and biculturalism within this group. Two hundred and eighty-six Mexican American undergraduates completed the Hamon Filial Responsibility Scale. Twenty others participated in focus groups. Females endorsed filial responsibility expectations at higher rates than males, but biculturalism influenced more cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…However, results in the opposite direction were found among Asian and Hispanic caregivers, indicating that 3rd generation Asian and Hispanic caregivers compared to their 1st generation counterparts, appeared to spend more hours. This pattern is consistent with some previous studies (Crist et al 2009;Kobayashi and Funk 2010;Rudolph et al 2011), and may be an indicator that traditional filial practices persist across generations, despite acculturation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, results in the opposite direction were found among Asian and Hispanic caregivers, indicating that 3rd generation Asian and Hispanic caregivers compared to their 1st generation counterparts, appeared to spend more hours. This pattern is consistent with some previous studies (Crist et al 2009;Kobayashi and Funk 2010;Rudolph et al 2011), and may be an indicator that traditional filial practices persist across generations, despite acculturation.…”
Section: Discussionsupporting
confidence: 92%
“…When controlling for sociodemographic variables and examining racial/ ethnic groups separately, only a comparison between 3rd generation non-Hispanic White caregivers and their 1st generation counterparts showed expected results, 3rd generation non-Hispanic White caregivers utilized significantly more respite care services compared to their 1st generation counterparts (p < .05). This finding was surprising because previous studies have shown some support for the researcher's hypothesis across these three racial/ethnic groups (Jolicoeur and Madden 2002;Rudolph et al 2011;Snowden and Yamada 2005;Young et al 2002). In contrast, 3rd generation Asian and Hispanic American caregivers used less respite care compared to 1st generation counterparts.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Supporting this hypothesis are studies that have found behavioral changes, such as less frequent contact and less likelihood to live nearby, between 1st and later generations of Asian (Ishii-Kuntz, 1997) and Hispanic caregivers (Rudolph, Chavez, Quintana, & Salinas, 2011; Rudolph et al, 2005). Subsequently, some researchers have raised questions about the needs of the next generations of caregivers and how these may differ from past generations (Anngela-Cole & Hilton, 2009; Kobayashi & Funk, 2010).…”
mentioning
confidence: 96%